The Role of Tolerance in Promoting Unity and Social Cohesion: Analytical Theoretical Study - AlDulaimi, Saleh Samer (Al-Adab Journal, 2023)
Tolerance is a great human principle and value that carries within it noble and precious meanings as it is the adornment of virtues and sits on the throne of other values. As Muslims, it is a good instinct that calls us to adhere to good manners and good deeds, and on top of it is tolerance.Our world today is in dire need of effective tolerance and positive coexistence between people more than ever, because the rapprochement between cultures and interaction between civilizations is increasing day by day thanks to the information and communication revolution and the technology revolution that removed the temporal and spatial barriers between nations and peoples until everyone lived in a cosmic village It is great, and tolerance in our time has become an indispensable necessity to achieve coexistence, stability and societal security.The research aims to identify the forms of tolerance and its role in achieving societal cohesion and stability, and its most important obstacles and effects on the individual and society.